Effect of electrode size on salinity-voltage correlation - Mohamed Aminuddin, Mai Mariam; Balasubramaniam, Manimekalai (Malaysia Technical Scientist Association (MALTESAS), 2016)
Malaysia is facing an energy crisis as local resources are depleting and there is a need to find alternative sources in order to overcome the shortcoming electricity crisis. Several researchers have initiated an investigation on the feasibility of salt as sources to generate electric. However, the study on the characteristic of salt as electric source has not well documented. Hence, this study investigated the correlation between salinity and electric voltage as well as the effect of electrode size on produced voltage. Based on the results, the generated voltage was linearly increased with the increased of salinity but significantly independence with the sizes of electrode used. The finding could be useful such as a guideline to develop a saltwater electric supply or to develop salinity measurement equipment in a liquid.